Workload, Motivation, and Their Influence on Nurse Performance: Evidence from Setio Husodo Hospital - Gultom, Juniati Bercita; Nurhasanah, Nurhasanah; Sagala, Lapiti (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This study investigates the influence of motivation and workload on nurse performance at Setio Husodo Hospital, Kisaran, Indonesia. The research addresses the fluctuating performance trends observed over five years and explores how motivational factors and workload management contribute to nursing service quality. Materials and methods: A quantitative descriptive approach was employed with 39 nurses selected through saturated sampling. Data were collected using validated questionnaires measuring motivation (12 items, α=0.853), workload (8 items, α=0.831), and nurse performance (8 items, α=0.847). Multiple linear regression analysis was conducted using SPSS version 22 to test hypotheses at a 5% significance level. Results: The regression model Y=1.282+0.286X₁+0.538X₂ demonstrated that both motivation (t=3.363, p=0.002) and workload (t=4.653, p=0.000) significantly influenced nurse performance. The simultaneous F-test (F=65.475, p=0.000) confirmed the combined effect of both variables. The adjusted R² of 0.772 indicates that 77.2% of performance variance is explained by motivation and workload, with workload showing stronger influence (β=0.548) than motivation (β=0.396). Conclusions: Motivation and workload are critical determinants of nurse performance in hospital settings. Healthcare administrators should implement balanced workload distribution strategies and robust motivational programs to optimize nursing service delivery and patient care quality.